Historical and democratic memory in the LOMLOE Primary Education curricula of the Spanish autonomous communities - García-Ruiz, Carmen Rosa; García-Morís, Roberto (Clio. History and History Teaching, 2024)
A significant innovation introduced by the LOMLOE (Organic Law Amending the Organic Law on Education) is the inclusion of democratic memory as a new dimension of citizenship education, aiming to enhance active citizen participation in public life. However, a study by Navarro-Medina, De Alba-Fernández and Pérez-Rodríguez (2023) identifies relevant omissions in the curriculum, including key concepts such as dictatorship, Francoism, totalitarian regime, persecution, exile and uprising. These gaps underscore the need to examine how Spain’s autonomous communities have interpreted the current education law. This research problem focuses on assessing the extent to which the political orientation of each community has influenced their interpretation of ministerial guidelines. To this end, we conduct a descriptive-interpretative analysis of the decrees regulating the primary education curriculum across the autonomous communities.
Keywords: historical memory; democratic memory; curriculum; primary education; autonomous communities.